The Research of Computational Method by Using Beam Element for Rope Structure. (October 2019) - He, Xuguang; Liang, Lin
Abstract: On the basis of in-depth study of mechanical behavior of rope, according to the catenary theory the equation of guy rope is built. Based on this equation, the guy rope is established in FEM which is analogized by using beam elements with little bending stiffness, and non-linear finite element calculations are applied for the guy rope. Take the theoretical shape of guy rope as study point, according to example calculations, computational accuracy about using beam element to simulate is quantificationally analyzed, and discipline curve of flexural rigidity to computational result is obtained and the results is also analyzed.